Clinical clustering of eight orthostatic haemodynamic patterns in The Irish Longitudinal Study on Ageing (TILDA) - Moloney, David (Age Ageing, 2020)
BACKGROUND: Orthostatic hypotension (OH) can be assessed with non-invasive continuous beat-to-beat haemodynamic monitoring during active stand (AS) testing; this yields large volumes of data outside the scope of the traditional OH definition. We explored clinical associations of different AS patterns in participants from Wave 1 of the Irish Longitudinal Study on Ageing. METHODS: AS patterns were generated based on three sequential binary systolic blood pressure features: drop ≥40 mmHg within 10 sec post-stand (“immediate deficit”), failure to return to within 20 mmHg of supine level at 40 sec after standing (“stabilisation deficit”) and drop ≥20 mmHg between >40 and 120 sec post-stand (“late deficit”). Eight AS groups resulted from combining the presence/absence of these three features. The groups were cross-sectionally characterised, and their ability to independently predict orthostatic intolerance (OI) during AS, and falls or syncope in the past year, was evaluated using multivariate logistic regression models. RESULTS: A total of 4,899 participants were included (mean age 61), of which 3,312 (68%) had no deficits. Older age was associated with stabilisation deficit and late deficits were seen in groups with higher proportions of beta blockers and psychotropic medications. Regression models identified independent associations between OI and three immediate-deficit groups; associations seemed stronger as more deficits were present. There was a significant association between falls history and the three-deficit group (odds ratio 1.54, 95% confidence interval: 1.15–2.07, P = 0.004). CONCLUSIONS: More deficits seemed associated with the higher risk of OI and falls history. Observations are not causal but the recognition of these patterns may help clinicians focus on careful prescribing.